Incidental finding of a Sertoli-Leydig cell tumor in a postmenopausal woman with complex endometrial hyperplasia - Kim, Yeejeong; Lee, In Ok; Chung, Jae Eun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Sertoli-Leydig cell tumors (SLCTs) arise from the non-germ cell component of the ovary and typically present in young women with evidence of hyperandrogenism such as precocious puberty, amenorrhea, hirsutism and virilization. It is very rare accounting for less than 0.2% of all ovarian tumors, and because of the rarity, no standardized treatment approach has reached a consensus. The prognosis is generally good with complete reversion of symptoms after surgery, although some cases have been reported to be malignant. Recently the need for DICER1 mutations testing in paediatric patients has been emphasized for the surveillance of possible synchronous tumors and affected family members. Authors present here a case of Sertoli-Leydig cell tumor incidentally found while performing a hysterectomy with bilateral salpingo-oophorectomy in a postmenopausal woman with endometrial hyperplasia that caused intractable vaginal bleeding.